Sistem Akuntansi Penerimaan dan Pengeluaran Kas pada Badan Usaha Milik Desa (BUMDES) Sumber Sejahtera Desa Pujon Kidul Kabupaten Malang - Sari, Amanda Meidina; Gunarianto, Gunarianto; Zaenudin, Zaenudin (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2024)
This research aims to determine and analyze the accounting system for cash receipts and disbursements at the BUMDes in Pujon Kidul Village, Malang Regency. The research approach used is descriptive qualitative, by describing the system applied in cash management, both receipts and expenditures. The research results show that the cash receipts accounting system at BUMDes Sumber Sejahtera has been designed by taking into account the principles of internal control, risk management and good accounts receivable management. The cash receipt procedure starts from recording by the cashier, verification by the financial supervisor, to deposit to the bank at the end of the working day, reflecting systematic and transparent management. Meanwhile, the cash disbursement accounting system shows the application of disciplined and structured procedures in accordance with accounting principles and internal control. Every cash disbursement begins with submitting a request accompanied by supporting documents, and must go through a verification and approval process by the authorized party. However, several things in the internal control system need to be improved, including, separation of organizational functions to avoid fraud and misappropriation of cash, improvements to the cash recording system because it does not comply with accounting standards such as journals, balance sheets and BUMDes financial reports in the general cash book.